Antibody persistence 7 years after hepatitis-A vaccine in children with human immunodeficiency virus infection - José G. Vázquez-Rosales; Alejandra P. Melgoza-Salazar; Mariana G. Sámano-Aviña; Victoria E. Montaño-Luna; Ma. Rosalía Lira-Carmona; Fortino Solórzano-Santos (Permanyer, 2024)
Background: HIV-infected children have a higher risk of presenting infections, including the hepatitis A virus (HAV). The inactivated HAV vaccine is immunogenic in immunocompetent hosts; however, there are insufficient studies on the duration of seroprotection in HIV-infected children. Methods: An analytical cohort study was conducted. HIV-1-infected children who received the inactivated HAV vaccine (2 doses) were included. Blood samples were taken for antibody measurement, the first one 28 days after the second dose and another 7 years after the vaccination schedule. Information on viral load, immunological category, weight, height, and response to antiretroviral treatment from diagnosis to the last assessment was obtained. Results: 19 patients were included, with a mean age of 12.6 years (SD ± 2.29). 58% were male. 80% of the patients presented protective immunoglobulin G antibodies against HAV 7-year post-vaccination. The antibody concentration was found to be between 13 and 80 mIU/mL (median of 80 mIU/mL). 52% showed some degree of immunosuppression. There was no statistically significant relationship between the presence of seroprotection and viral load, treatment failure, immunological category, and malnutrition. Twelve patients presented with antiretroviral treatment failure, and in 33% of them, the antibodies did not offer satisfactory seroprotection. Conclusion: 7-year post-vaccination, 80% of HIV-infected children maintain seroprotection titers against HAV.